(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
The control of odors and dust emissions in production systems is crucial for ensuring environmental sustainability, worker health, and regulatory compliance. This article presents a comprehensive review of various odor and dust filtering systems implemented in production processes. The effective control of odors and dust emissions in production systems is essential for ensuring a clean and healthy working environment, compliance with regulations, and environmental sustainability. This abstract provides an overview of various odor and dust filtering systems employed in production processes. The objective of this study is to assess the efficiency and suitability of different filtration technologies in addressing odor and dust-related challenges. Electrostatic precipitators, activated carbon filters, cyclone separators, and other advanced systems are evaluated in terms of their filtration performance, reliability, and cost-effectiveness. The findings reveal that the implementation of these diverse filtration systems significantly reduces odors and removes airborne dust particles, leading to enhanced air quality within production facilities. This contributes to improved worker health and safety, as well as reduced environmental impact. The implications of these results extend beyond specific industries, serving as valuable insights for other sectors grappling with similar issues. By adopting these proven filtration technologies, companies can meet regulatory requirements, minimize their ecological footprint, and demonstrate their commitment to sustainable practices.